2018
DOI: 10.1534/genetics.118.301516
|View full text |Cite
|
Sign up to set email alerts
|

Selection-Like Biases Emerge in Population Models with Recurrent Jackpot Events

Abstract: Evolutionary dynamics driven out of equilibrium by growth, expansion, or adaptation often generate a characteristically skewed distribution of descendant numbers: the earliest, the most advanced, or the fittest ancestors have exceptionally large number of descendants, which Luria and Delbrück called "jackpot" events. Here, I show that recurrent jackpot events generate a deterministic median bias favoring majority alleles, which is akin to positive frequency-dependent selection (proportional to the log ratio of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 44 publications
5
46
0
Order By: Relevance
“…Thus, the analysis of genomic data from organisms characterized by highly skewed offspring distributions-such as viruses-may be prone to serious misinference if examined with traditional WF and Kingman based approaches, even under neutrality. In particular, the neutral multiple merger events induced by the reproductive biology of these organisms may be mistaken for multiple-merger events induced by positive selection (Hallatschek 2018).…”
mentioning
confidence: 99%
“…Thus, the analysis of genomic data from organisms characterized by highly skewed offspring distributions-such as viruses-may be prone to serious misinference if examined with traditional WF and Kingman based approaches, even under neutrality. In particular, the neutral multiple merger events induced by the reproductive biology of these organisms may be mistaken for multiple-merger events induced by positive selection (Hallatschek 2018).…”
mentioning
confidence: 99%
“…Beyond high-variance reproduction, many other phenomena can lead to multifurcations in the ancestral process of a sample, such as repeated selective sweeps (Durrett and Schweinsberg 2004), strong selective pressure (Neher and Hallatschek 2013), or oversampling (Bhaskar, Clark, and Song 2014). Using classical methods to analyze such datasets can lead to systematic biases (Hallatschek 2018; Sackman, Harris, and Jensen 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical work has demonstrated that fat‐tailed distributions of descendants with infinite variance can lead to qualitatively different population genetic dynamics (Der et al, ; Eldon & Wakeley, ; Hallatschek, ; Schweinsberg, ). While our experimentally determined distributions are fatter than log‐normal, it is unlikely that the variance diverges with population size for the particular species and conditions we examined.…”
Section: Resultsmentioning
confidence: 99%
“…However, for some animals there is high variance in reproductive success, with a minority of males fathering a large fraction of the children in each generation (Araki, Waples, Ardren, Cooper, & Blouin, 2007;Hedgecock, 1994;Hedgecock & Pudovkin, 2011;Lallias, Taris, Boudry, Bonhomme, & Lapègue, 2010). Such highly skewed offspring distributions have fundamental implications for how we predict and interpret fluctuations in allele frequencies (Der et al, 2012;Eldon & Wakeley, 2006;Hallatschek, 2018;Hedrick, 2005;Hoban et al, 2013;Schweinsberg, 2003). These implications include dramatic (e.g.…”
mentioning
confidence: 99%